The work, workforce, technology and organisational implications of the '111' single point of access telephone number for urgent (non-emergency) care: a mixed-methods case study - Joanne Turnbull; Catherine Pope; Alison Rowsell; Jane Prichard; Susan Halford; Jeremy Jones; Carl May; Valerie Lattimer (National Institute for Health Research, 2014)
Background: NHS 111 represents a fundamental change in the way that urgent care is delivered. It is underpinned by a computer decision support system (CDSS) and involves significant labour substitution, in particular the greater use of non-clinical staff to deliver services. Objective: To investigate four core features of health-care innovation and change in relation to the new NHS 111 telephone-based service for 24/7 access to urgent care, namely the way in which work and workforce are organised for this new service and how the technology and organisational context shape the way in which services are delivered. Design: Comparative mixed-methods case study of NHS 111 providers. Settings: Five NHS 111 sites, characterised by differences in organisational size, form and ethos and in the type of workforce employed and professional roles and skill mix. Methods: The study combined ethnographic and survey methods. Non-participant observation was conducted at NHS 111 call centres and their linked urgent care centre(s) (UCCs; a total of 356 hours). Six focus groups were conducted with 47 call advisers, clinicians and organisational managers. An online survey was administered to call centre and UCC staff (n = 745) to ask their views about NHS 111; trust in NHS Pathways; and communication and information sharing (response rate: 41% for call centre staff, 35% for UCC staff). Results: Clinical assessment by call advisers is characterised by high levels of communication (including negotiation, communication and translation) and 'emotion' work, extending the work beyond simple operation of a CDSS. At most sites clinical advisers supported call advisers in clinical assessment but also played an important role in managing and sanctioning dispositions, notably emergency ambulance dispositions. Clinicians at UCCs have experienced a loss of control over their everyday work, which is now shaped by call centre workers. The Directory of Services, which provides information about locally available services, is key to delivering an integrated urgent care system. Trust in the CDSS is higher amongst call advisers than amongst clinical staff but there is widespread belief that the CDSS is risk averse. Staff often develop workarounds to 'make the technology work'. There is considerable variation in how NHS 111 is organised and delivered, shaped by the organisational history and the professional culture of the organisations involved. Some sites were driven more by rationing and systemising, pursuing the NHS 111 vision of 'right care, right place, right time', whereas others were driven more by an ethos of what they perceived was a more patient-centred service. Conclusions: NHS 111 is primarily founded on a network of different organisations providing different aspects of the service. This network is primarily enabled through technological integration. Successful integration also requires understanding and trusting relationships between different providers, which were lacking in some sites. Underpinning NHS 111 with non-clinical workers offers significant opportunities for workforce reconfiguration, but this is not a simple substitution of labour (i.e. non-clinical staff replacing clinical staff). There is a significant organisational structure that is necessary to support and 'keep in place' both the CDSS itself and non-clinical workers using the CDSS. Funding: The National Institute for Health Research Health Services and Delivery Research programme.